Gaia-4b and 5b: Radial Velocity Confirmation of Gaia Astrometric Orbital Solutions Reveal a Massive Planet and a Brown Dwarf Orbiting Low-mass Stars - Gudmundur Stefánsson; Suvrath Mahadevan; Joshua N. Winn; Marcus L. Marcussen; Shubham Kanodia; Simon Albrecht; Evan Fitzmaurice; Onė Mikulskytė; Caleb I. Cañas; Juan I. Espinoza-Retamal; Yiri Zwart; Daniel M. Krolikowski; et al. (The Astronomical Journal)
Gaia astrometry of nearby stars is precise enough to detect the tiny displacements induced by substellar companions, but radial velocity (RV) data are needed for definitive confirmation. Here we present RV follow-up observations of 28 M and K stars with candidate astrometric substellar companions, which led to the confirmation of two systems, Gaia-4b and Gaia-5b, identification of five systems that are single lined but require additional data to confirm as substellar companions, and the refutation of 21 systems as stellar binaries. Gaia-4b is a massive planet ( M  = 11.8 ± 0.7 M _J ) in a P  = 571.3 ± 1.4 day orbit with a projected semimajor axis a _0  = 0.312 ± 0.040 mas orbiting a 0.644 ± 0.02 M _⊙ star. Gaia-5b is a brown dwarf ( M  = 20.9 ± 0.5 M _J ) in a P  = 358.62 ± 0.20 days eccentric e  = 0.6423 ± 0.0026 orbit with a projected angular semimajor axis of a _0  = 0.947 ± 0.038 mas around a 0.34 ± 0.03 M _⊙ star. Gaia-4b is one of the first exoplanets discovered via the astrometric technique, and is one of the most massive planets known to orbit a low-mass star.